The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313477
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Learning for Unsupervised Influenza-like Illness Models from Online Search Data

Abstract: A considerable body of research has demonstrated that online search data can be used to complement current syndromic surveillance systems. The vast majority of previous work proposes solutions that are based on supervised learning paradigms, in which historical disease rates are required for training a model. However, for many geographical regions this information is either sparse or not available due to a poor health infrastructure. It is these regions that have the most to benefit from inferring population h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…As input for the proposed model, we selected the top L English search queries for the US, AU, and UK based on the list, and selected each search query in JP and FR corresponding to the English search query based on these one-to-one query mapping methods. The usefulness of mapping from English to other languages is described in [33,50,53]. These studies pointed out that the volume movement in the search queries is similar among countries with certain health conditions.…”
Section: Methods For Finding Search Queriesmentioning
confidence: 99%
See 2 more Smart Citations
“…As input for the proposed model, we selected the top L English search queries for the US, AU, and UK based on the list, and selected each search query in JP and FR corresponding to the English search query based on these one-to-one query mapping methods. The usefulness of mapping from English to other languages is described in [33,50,53]. These studies pointed out that the volume movement in the search queries is similar among countries with certain health conditions.…”
Section: Methods For Finding Search Queriesmentioning
confidence: 99%
“…Many methods using UGCs for forecasting the flu volume have been developed since the emergence of Google Flu [18], which demonstrated that the number of search queries capturing human behaviors was a good resource for forecasting. Certain studies [21,49,53,48] have depended on "Google Correlate," which returns English search queries that are the most highly correlated to an input time series, for the selection of suitable search queries. However, this approach cannot be used in many areas (non-English-speaking areas) and it has already been unavailable since December 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some attempts in this research direction [26]. Transfer learning deals with training a model for a given problem and using it to related but different problem [81]. Transfer learning has been applied for the prediction of confirmed cases by using the model trained on data from one country in which is ahead in the epidemic curve to other countries still in earlier stages of the epidemic curve [73].…”
Section: Suggestionsmentioning
confidence: 99%
“…Resource selection for the prediction method is also an important factor in influenza prediction. Many studies have relied on user-generated content (UGC) from internet services, such as search services [12,14,23,24] and social networking services [25][26][27]. Infectious disease surveillance conducted with online content, such as that described above, is generally described as infoveillance [28].…”
Section: Plos Onementioning
confidence: 99%